Indicadores epidemiológicos, operacionais, distribuição espacial e espaço-temporal dos casos de hanseníase na Paraíba - Véras, Gerlane Cristinne Bertino (2023)
Leprosy remains eingb a public health problem in Brazil and, particularly, in Paraíba, which indicates the need to carry out actions more faithfully to the local reality, therefore it is essential the use of analysis techniques that can identify the areas of lower and greater vulnerability to the disease of the population. Thus, the objective was to analyze the epidemiological and operational indicators, the spatial and space-temporal distribution of new cases of leprosy. This is an ecological type of study, with a quantitative approach with the using of secondary data and spatial and space-temporal analysis. The locus of the study was the state of Paraíba, having as units of analysis its 223 municipalities. The database consisted of 2,468 new cases of leprosy notified in the period of 2016 to 2020, in addition to 1,128 cases corresponding to the cohort years (2014 and 2015), according to the need to build each indicator. The data were provided by the State Secretarial of Paraíba after approval by the Research Ethics Committee. The number of inhabitants residing in the municipalities was collected on the website of the Department of Informatics of the Unified Health System and the territorial network of the Brazilian Institute of Geography and Statistics. Data were analyzed according to the descriptive statistics and through spatial and space-temporal analysis, using five epidemiological indicators and five operational of leprosy, of the Scan sweep, of the spatial rate ratio, of the spatial proportions ratio, of the space-temporal average ratio and of the space-temporal median ratio, using the R statistical program. New cases of leprosy were found more incidentally in men (54.8%), aged between 40 and 49 (19.3%), self-declared brown color/race (63.6%), with incomplete primary education (51.4%), housing at the urban area (82.5%), in housewives (12.5%), that presented from one to five skin lesions (46.9%), borderline clinical form (31.2%), classification multibacillary (64.8%), degree of physical disability 0 at the diagnosis (51.0%) and at the discharge (22.7%), which were detected by referral (65.5%), negative bacilloscopy (28.6%), without affected nerve (44.9%), without leprosy reaction (36.5%) and who were discharged due to cure (61.3%); as well as formation of simple and compound conglomerates specially in the East and West of the state; general detection rate of new cases (12.0), of those under 15 years (3.1); and the proportion of cases with physical disability degree 2 at diagnosis (10.6%) of high parameters; the rate of new cases with physical disability degree 2 indicated an increase in the magnitude of the disease; the proportion of examined contacts (61.4%) and of cured cases with assessed degree of physical disability (49.4%) presented precarious parameters; the proportion of cure among new cases and of new cases with assessed degree of physical disability (81.1%) had a regular parameter (80.8%); and the good parameter abandonment (5.5%); moreover, it appears that the proposed techniques are viable and efficient for identifying the municipalities that most contribute to the leprosy situation in the state. It is suggested that the public authorities recognize leprosy as a priority disease and implement public policies that include several agencies in partnership with the health, in order to change the local reality of facing the leprosy.